VOCATIONAL STUDENTS’ SATISFACTION OF THE SYNCHRONOUS ONLINE LEARNING IN LAO LANGUAGE COURSE - Dao, Shiqi; Phongsatha, Satha (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2024)
Purpose: As the backdrop of this reaseach is online teaching via asynchronous online learning, this research examined the factors and effects of intrinsic motivation (IML), perceived interactivity (PI), attitude (AT), and perceived ease of use (PEU) on satisfaction with learning among students of Laotian language courses in vocational colleges. Design Data and Methodology: Employing a questionnaire survey, data were collected from 57 students majoring in Laotian language at a vocational and technical college in Yunnan Province— 16 males and 41 females. Multiple linear regression analysis was conducted to analyze the data. Results: The study revealed that student satisfaction was influenced by factors such as intrinsic motivation (IML), perceived interactivity (PI), and perceived ease of use (PEU). Specifically, perceived interactivity (PI) exerted the greatest influence on student satisfaction, explaining 65.9% of the variance (β=.659, p<.001), which was statistically significant. However, attitude (AT) did not significantly impact student satisfaction (β = -.543, p<.001). Conclusion: In conclusion, integrating students’ perceived ease of use into the teaching process during online Laotian language instruction via asynchronous online learning could enhance student satisfaction. Such an online teaching mode could facilitate positive interactions between students and teachers as well as among students themselves.